PENGARUH WAKTU PERENDAMAN IKAN ASIN SELAR KUNING (Selaroides leptolepis) DALAM AIR LERI PEKAT TERHADAP DEGRADASI FORMALIN - Angki Purwanti; Tri Prasetyorini; Bagya Mujianto (Poltekkes Kemenkes Jakarta III, 2017)
From the previous study formalin in salted pepetek fish can be degraded by 66% after soaking in leri water for 60 minutes. The magnitude of formalin degradation depends on the type of salted fish and the concentration of leri water . This study aims to obtain an optimal immersion time from formalinized selar kuning salted fish, to produce maximum formalin degradation but still good in terms of organoleptic.Samples of selar kuning salted fish are made by soaking 2 kg of selar kuning fish in formalin 10% for 24 hours. Drained and re-soaked in 40% salt solution for 12 hours then dried under direct sun. Formaldehyde levels were determined after the sample was immersed in concentrated leri water with time variations (0.10, 20, 30 and 40) minutes. Measurement of formalin content was done colorimetrically with chromotropic acid reagent at λ 540 nm. Organoleptic selar kuning salted fish samples are still good after soaking 40 minutes inconcentrated leri water. The average content of formalin after soaking in concentrated leri water during (0, 10, 20, 30 and 40) minutes was (13.94, 11.44, 10.03, 10.82 and 13.31) ppm and its formalin degradation was (0, 17.92, 28, 22 and 4.48)%. When the immersion time is more than 20 minutes then the formalin content in the sample rises again due to re-forming the bond between aldehyde groups in formalin with proteins present in salted fish. The optimal immersion time in optimal concentrated water for selar kuning salted fish is 20 minutes resulting in 28% formalin degradation. For people who will consume selar kuning salted fish, before cooked first soak in leri water concentrated for 20 minutes and immediately removed from the water immersion